Portfolio-based Analysis and Competencies of Hospitality Management Students in Events Management: A Basis for Syllabus Enrichment - Pioquinto, Bernie; Camara, Jun; Buted, Dexter R; Espinosa, Nieva (Asian Journal of Multidisciplinary Studies, 2019)
Skill competence is the central ingredient of the market, and identifying its level prior immersion is a vital labor-oriented principle. This study aimed to identify the level of competence of Hospitality Management (HM) Students in PSU – Lingayen in Events Management in major indicators, namely, Company Profiling and Bidding Process. Using a mixed method of research by triangulating survey-questionnaire results with documentary content analysis, findings showed that the HM students are generally competent. However, areas of weakness which are considered as opportunities for improvement are found including the need to require students to write business legal documents like memoranda of understanding and agreement, among others. Recommendations to integrate the findings in existing TEC 109 Events Management Syllabi are advised in Course Outcomes 6 (Event Proposal), 7 (Communication letters), and 9 (On-site Event).